OCP002, a Mixed Agonist of Opioid and Cannabinoid Receptors, Produces Potent Antinociception With Minimized Side Effects. (1st December 2022) - Xu, Biao; Zhang, Qinqin; Chen, Dan; Zhang, Mengna; Zhang, Run; Zhao, Weidong; Qiu, Yu; Xu, Kangtai; Xiao, Jian; Niu, Jiandong; Shi, Yonghang; Li, Ning; et al.
Abstract : BACKGROUND: Increasing attention has been attracted to the development of bifunctional compounds to minimize the side effects of opioid analgesics. Pharmacological studies have verified the functional interaction between opioid and cannabinoid systems in pain management, suggesting that coactivation of the opioid and cannabinoid receptors may provide synergistic analgesia with fewer adverse reactions. Herein, we developed and characterized a novel bifunctional compound containing the pharmacophores of the mu-opioid receptor agonist DALDA and the cannabinoid peptide VD-Hpα-NH2, named OCP002. METHODS: The opioid and cannabinoid agonistic activities of OCP002 were investigated in calcium mobilization and western blotting assays, respectively. Moreover, the central and peripheral antinociceptive effects of OCP002 were evaluated in mouse preclinical models of tail-flick test, carrageenan-induced inflammatory pain, and acetic acid–induced visceral pain, respectively. Furthermore, the potential opioid and cannabinoid side effects of OCP002 were systematically investigated in mice after intracerebroventricular (ICV) and subcutaneous (SC) administrations. RESULTS: OCP002 functioned as a mixed agonist toward mu-opioid, kappa-opioid, and cannabinoid CB1 receptors in vitro. ICV and SC injections of OCP002 produced dose-dependent antinociception in mouse models of nociceptive (the median effective dose [ED50 ] values with 95% confidence interval [CI] are 0.14 [0.12–0.15] nmol and 0.32 [0.29–0.35] μmol/kg for ICV and SC injections, respectively), inflammatory (mechanical stimulation: ED50 values [95% CI] are 0.76 [0.64–0.90] nmol and 1.23 [1.10–1.38] μmol/kg for ICV and SC injections, respectively; thermal stimulation: ED50 values [95% CI] are 0.13 [0.10–0.17] nmol and 0.23 [0.08–0.40] μmol/kg for ICV and SC injections, respectively), and visceral pain (ED50 values [95% CI] are 0.0069 [0.0050–0.0092] nmol and 1.47 [1.13–1.86] μmol/kg for ICV and SC injections, respectively) via opioid and cannabinoid receptors. Encouragingly, OCP002 cannot cross the blood-brain barrier and exerted nontolerance-forming analgesia over 6-day treatment at both supraspinal and peripheral levels. Consistent with these behavioral results, repeated OCP002 administration did not elicit microglial hypertrophy and proliferation, the typical features of opioid-induced tolerance, in the spinal cord. Furthermore, at the effective analgesic doses, SC OCP002 exhibited minimized opioid and cannabinoid side effects on motor performance, body temperature, gastric motility, physical and psychological dependence, as well as sedation in mice. CONCLUSIONS: This study demonstrates that OCP002 produces potent and nontolerance-forming antinociception in mice with reduced opioid- and cannabinoid-related side effects, which strengthen the candidacy of bifunctional drugs targeting opioid/cannabinoid receptors for translational-medical development to replace or assist the traditional opioid analgesics.